Fracking and Goldilocks Federalism: the too loud, too quiet and just right politics of states and cities - Fisk, Jonathan M., author; Davis, Charles E., advisor; Opp, Susan M., committee member; Straayer, John A., committee member; Shelley, Tara O'Connor, committee member (Colorado State University. Libraries, 2015)
Wicked environmental and energy challenges often originate where energy, the environment and economics intersect (Rittel and Webber 1973). Fracking is one such example. As a practice, it has prompted a certain amount of political debate at both the state and municipal levels. Proponents argue that natural gas extraction creates well-paying jobs, helps grow and revive stagnant economies and that it provides a 'cleaner' burning energy source. Its opponents counter that the technique produces a number of environmental harms such as air pollution, surface and groundwater contamination, places new demands on infrastructure and causes geological instability (Davis 2012). Ranging from intergovernmental battles to cooperative relationships, the politics of fracking are reshaping the relations between neighborhoods, city hall and the statehouse. To explore the 'second order' dynamics of fracking, this dissertation asks several interrelated questions. What are the state and local institutions, rules and informal norms governing state-municipal relationships when it comes to hydraulic fracturing? To what extent do municipalities regulate fracking and what are the types of city-level regulation? Finally, why are some cities willing to pass land use policies that challenge their state's natural gas extraction goals and preemptive authority and others are not? To answer the questions above, I consider the second order dynamics in the context of Colorado, Texas and Ohio and a sample of cities in each state. Each state has a high number of citizens living near gas wells, but offers cities and towns varying degrees of land use authority. To elucidate their second-order relationships and dynamics, each chapter tests potential explanatory variables originating from studies of environmental policy, democratic theory and urban governance. Results suggest that both macro level (environmentalism and mobilization) and micro level concerns (percentage of owner occupied homes and median home values) can affect second order relations and the willingness of local communities to exert more municipal autonomy and challenge their state. My findings offer a more complete picture of second order federalism and strengthen the scholarly and applied understanding of two key American political institutions.
Keywords: fracking; natural resources; state politics; municipal politics; environmental policy; second order federalism